A study to assess the knowledge regarding bio-medical waste management among the staff nurses working in selected hospital, Siliguri - Sarkar, Seema; Khati, Prerna; Choudhury, Susmita; Saha, Anwesa; Das, Rima; Mandal, Gouri; Mondal, Nabanita; Barman, Keya; Banerjee, Oyndrima; Khatun, Sabia; Das, Sayani; Mondal, Priyanka; et al. (International Journal of Research in Medical Sciences, 2022)
Background: Biomedical waste (BMW) management have become a significant concern for health care providers as it carries a higher potential for infection and injury. Inappropriate knowledge of handling of healthcare waste may have serious health consequences. There is an urgent need for raising awareness of BMWM among the hospital staff in all healthcare setups. Effective management of biomedical waste is not only a legal necessity but also a social responsibility. Objective was to assess the knowledge of staff nurses regarding biomedical waste management and to find out the association between the level of knowledge of the staff nurses regarding BMW management with selected demographic variables. Methods: A descriptive cross-sectional study, was conducted in March 2022. Study participants were the nursing staff, who are dealing with BMW. The data was collected by using a semi-structured questionnaire. Results: 50% of staff nurses were having a good knowledge, 20% of them had poor knowledge. Significant relationship was found to be exist between knowledge regarding bio-medical waste management with qualification and the duration of their clinical practices (p<0.05). Conclusions: Staff nurses have direct contact with bio-medical waste so they must be made aware of the risk of blood-borne infection and the main emphasis must be given to prevent such infections by using personal protective devices and regular training and supervision is necessary for better healthcare waste management and implementation.